A planar supercapacitor made of supramolecular nanofibre based solid electrolyte exhibiting 8 V window. (July 2019) - Kundu, Suman; Mogera, Umesha; George, Subi J.; Kulkarni, Giridhar U.
Abstract: Planar microsupercapacitors are emerging as essential devices for rapid energy sourcing in on-chip circuitry. A serious limitation in comparison to planar microbatteries is the energy density that a planar supercapacitor can offer (∼two orders less), which in turn relates to the maximum working potential of the electrolyte used in it, which is typically below 3 V. In this article, we report the fabrication of a planar supercapacitor with an operating voltage window, highest among the reported till date. The electrolyte used is essentially a solid in the form of nanofibres of a supramolecular donor-acceptor assembly, consisting of coronene tetracarboxylate salt (CS) and dodecyl methyl viologen (DMV), carrying positive (K + ) and negative (Br − ) ionic charges, respectively. The fibres are drop-spread across Ti microgap electrodes and the device is operated in the ambient or in a humidity-controlled cell. The device is found stable up to a working potential window of 8 V, exhibiting areal capacitance values of 0.2 mF/cm 2 under room humidity conditions (RH, 65%) which was enhanced to 9.5 mF/cm 2 under 90% RH in presence of hygroscopic KBr crystallites. The estimated areal energy and power density values are remarkable, 85 μWh cm −2 and 24.7 W cm −2 respectively. The device retained 86% capacitance even after 50000 charge-discharge cycles. Using a single device, AC line filtering is shown possible with ripple less than 5%. These extraordinary properties are borne out of the facile diffusion of ions along the 1D face-to-face arrangement of the D-A molecules in the nanofibres while the ambient oxide covered Ti surface providing the required electrochemical stability to the device. Graphical abstract: A new type of solid electrolyte offers voltage window of 8 V. With supramolecular nanofibres as solid electrolyte spread on titanium metal electrodes, the planar supercapacitor formed offers a voltage window of 8 V, surpassing all conventional designs limited to typically below 3.5 V. Image 1 Highlights: A planar supercapacitor with supramolecular nanofibre electrolyte on Ti electrodes has been fabricated. The device works with a voltage window of 8 V at a capacitance of 9.5 mF/cm 2 with capacitance retention of 86%. It exhibits a very high scan rate stability of 10000 V/s. The areal energy density is 85 μWh cm −2 and the power density, 24.7 Wcm −2 . Single device can filter AC line signals (8 V) with negligible ripple.